Long‐Chain Hyperbranched Polymers: Synthesis, Properties, and Applications. Issue 17 (5th September 2019) - Mu, Bin; Liu, Tingting; Tian, Wei
Abstract : Outside Back Cover : In article number1800471, Wei Tian and co‐workers synthesize long‐chain, hyperbranched polymers featuring a linear polymeric subchain segment between branching points within a threedimensional, highly‐branched macromolecule.